German minority teaching in Poland in German online discourse - Ziaja, Ryszard (Papers in Linguistics, 2026)
German minority teaching (Deutsch als Minderheitensprache, DaM) is now an integral part of the Polish education system. Particularly in the Upper Silesia region, students have been learning German in this form of instruction for many years. The multi-layered structure of German minority teaching as well as the inconsistent linguistic and cultural learner profile characterise the current situation of DaM in Poland. Thus, it becomes a matter of interest how it is perceived in German media discourse and what image of DaM can be identified in the German cultural and linguistic community as a result. The article attempts to analyse the discursive world view of DaM in Poland on the basis of German-language online texts. The analysis is based on proven methodological approaches of frame theory. The discursive world view scrutinised this way is contrasted with the current legal and social situation of DaM teaching in Poland in order to reveal culturally specific findings of particular relevance for the Polish education system and learner profile.